Identification of circular RNA‐associated competing endogenous RNA network in the development of cleft palate. Issue 9 (9th May 2019) - Shu, Xuan; Cheng, Liuhanghang; Dong, Zejun; Shu, Shenyou
Abstract: Circular RNAs (circRNAs) serve as competing endogenous RNAs (ceRNAs) and indirectly regulate gene expression through shared microRNAs (miRNAs). However, the regulatory mechanisms of circRNA as ceRNA associated with the fusion of palatal shelves in palatogenesis are yet unclear. This study aimed to explore the potential mechanism underlying the role of circRNA as ceRNA in cleft palate (CP). First, we systematically analyzed RNA‐seq and miRNA‐seq data after high‐throughput sequencing for embryonic palatal shelf tissues from a mouse CP model induced by maternal exposure to all‐trans retinoic acid on embryonic gestation day 14.5 (E14.5). Thirty‐nine circRNAs, 18 miRNAs, and 936 messenger RNAs (mRNAs) were significantly dysregulated (log2 [fold change FC] > 1; P < 0.05). Thereafter, we constructed a circRNA‐associated ceRNA network. Finally, we determined the circRNA_0954–miRNA‐881‐3p‐PRKAR1α ceRNA network as a hub involved in palatogenesis. Gene Ontology analysis revealed that ceRNA‐related genes were associated with facial morphogenesis and developmental gene silencing. Kyoto Encyclopedia of Genes and Genomes pathway analysis indicated that ceRNA‐related genes are involved in apoptosis ( P < 0.05, fold enrichment >1). Quantitative reverse transcription polymerase chain reaction was performed to verify the results of ceRNA analysis. We found that the circRNA‐miRNA‐mRNA ceRNA network is involved in palatogenesis. The present results imply that circRNA_0954‐miRNA‐881‐3p‐PRKAR1α ceRNA network may cause dysfunctional palatal fusion and might facilitate the development of novel epigenetic biomarkers to treat CP in the future. Abstract : This study aimed to explore the potential mechanism underlying the role of circular RNA (circRNA) as competing endogenous RNA (ceRNA) in cleft palate. We found that a circRNA‐miRNA‐mRNA ceRNA network is involved in palatogenesis and it may cause dysfunctional palatal fusion and might facilitate the development of novel epigenetic biomarkers to treat cleft palate in the future. We believe that our study makes a significant contribution to the literature because it provides novel insights into the treatment of cleft palate.